SHIFT FROM THE CENTRAL PLACE THEORY TO THE URBAN NETWORK THEORY IN URBAN SYSTEMS RESEARCH - Coteli, Methiye Gul; Yenen, Zekiye (YILDIZ TECHNICAL UNIV, 2012)
Cities, permanently tending to establish relationships, interactions, and connections with the discontinuous or immediate hinterland and evolving to a place of flows, are systems that determine their own economic influence area within the system of cities. According to the unsteady geographic movement of the surplus, not only for the city the shift is inevitable, but also for the whole urban system. In order to determine the shift in an urban system, the methods of production, distribution, transportation, consumption, and governance should be focused. The main purpose of this article is to evaluate the framework that was drawn by central place theory and network model, which have been suggested to explain the spatial structure and organization of urban systems, by taking a comparative approach. The term of system of cities describes the hierarchical classification of integrated and co-operated cities together, but urban network expresses interdependence and the degree of connectivity into the network. If the analysis of a city within the urban system will be done, it is necessary to situate the city within the nested set of spatio-temporal scales and the possible levels of analysis. One of the most important results of this study is that one-sided vertical relationships seen between an accessible centre, which is responsible for the distribution of urban functions and hinterland, according to Central Place Theory. As to Network Theory, the city taking a central role in the serving region functions as nodal point providing horizontal and vertical relationships with cities because of its connections extend beyond umland on trade and communication networks. By considering the factors of centrality, connectivity and complementarity in functions, the emergence of the urban system as an urban network is clearly evident through the examples in history. The global city of historical urban network is the city that enables the circulation of a strategic product through the urban network and by this way gets the feature of connectivity.
Keywords: Urban system; urban network; hinterland; central place theory; network theory; PARADIGM; CITIES; Engineering